No sex differences in learning in wild bumblebees. (29th March 2021) - Muth, Felicity; Tripodi, Amber D; Bonilla, Rene; Strange, James P; Leonard, Anne S
Abstract: Females and males often face different sources of selection, resulting in dimorphism in morphological, physiological, and even cognitive traits. Sex differences are often studied in respect to spatial cognition, yet the different ecological roles of males and females might shape cognition in multiple ways. For example, in dietary generalist bumblebees ( Bombus ), the ability to learn associations is critical to female workers, who face informationally rich foraging scenarios as they collect nectar and pollen from thousands of flowers over a period of weeks to months to feed the colony. While male bumblebees likely need to learn associations as well, they only forage for themselves while searching for potential mates. It is thus less clear whether foraging males would benefit from the same associative learning performance as foraging females. In this system, as in others, cognitive performance is typically studied in lab-reared animals under captive conditions, which may not be representative of patterns in the wild. In the first test of sex and species differences in cognition using wild bumblebees, we compared the performance of Bombus vancouverensis nearcticus (formerly bifarius) and Bombus vosnesenskii of both sexes on an associative learning task at Sierra Nevada (CA) field sites. Across both species, we found that males and females did not differ in their ability to learn, although males were slower to respond to the sucrose reward. These results offer the first evidence from natural populations that male bumblebees may be equally as able to learn associations as females, supporting findings from captive colonies of commercial bees. The observed interspecific variation in learning ability opens the door to using the Bombus system to test hypotheses about comparative cognition. Abstract : Males and females often differ in their cognitive abilities. Since female bumblebees might visit thousands of flowers a day, while males only forage for themselves, we expected that females would be better at learning floral associations. Across two species tested for the first time in the wild, we uncovered evidence for species difference but found that the sexes did not differ in learning ability.